Pengaruh Model Problem Based Learning Berbantuan Kahoot! Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas VIII SMP - Tauchid, Mauli Azkia; Baidowi, Baidowi; Junaidi, Junaidi (Griya Journal of Mathematics Education and Application, 2025)
Mathematical concept understanding ability is an essential aspect of mathematics learning, however in reality many students still face difficulties in comprehending basic mathematical concepts. One of the factors causing this issue is the dominance of conventional teaching models that do not actively engage students. Therefore, the research aims to examine the effect of applying the Problem Based Learning model assisted by Kahoot! on students’ mathematical concept understanding abilities in class VIII. This research employs a Quasi Experimental method with a quantitative approach and a posttest only non-equivalen control group design. The sample is selected using the purposive sampling technique, with class VIII 6 as the experimental class, which receives treatment in the form of the PBL model assisted by Kahoot!, and class VIII 2 as the control class, which is taught using the direct instruction model assisted by Kahoot!. Based on the t-test calculation, the obtained value was > with 8,712 > 1,672. Moreover, the effect size test results show a value of 1,052, categorized as high, meaning there is an effect of the Problem Based Learning model assisted by Kahoot! on the mathematical concept understanding abilities in class VIII.